Fast Delayed Signal Cancellation Based Pll for Unbalanced Grid Conditions - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2018)
Frequency identification is one of the most critical issues for grid-connected power converters, especially when the grid is unbalanced or distorted. Therefore, this paper proposes a novel frequency estimator with fast convergence for balance and unbalanced grid-voltage faults. The proposed algorithm is based on a Phase Locked Loop (PLL), enhanced with a fast positive and negative sequence detector. Delayed Signal Cancellation methodology with fast convergence is investigated under single-phase and two-phase voltage dip. The effectiveness of the proposed PLL is validated using simulations and experimental results. © 2018 IEEE.